Net positive : how courageous companies thrive by giving more than they take - Polman, Paul, (Harvard Business Review Press, 2021)
"Runaway climate change and persistent inequality are ravaging the world and humanity. Who can help lead us to a better future? Business. These massive dual challenges-and other profound shifts like pandemics, resource constraints, and shrinking biodiversity-threaten our very existence on the planet. Yet division and discord risk undermining our response, just when we need to come together. Global partnership and leadership are lacking, free trade and globalization are under attack, and populism continues to breed intolerance and disruption. At this critical time in history, the imperative to reimagine our economies and companies could not be more urgent. Fortunately, many in the business community-from large corporations to microenterprises-are helping to solve our most profound challenges by deploying long-term, purpose-led business models that put people and planet first. And they are profiting on this new path with new tools, AI and data-driven transparency, and radical improvements in the economics of clean technologies. The key question has flipped from "Why would you do sustainability?" to "Why wouldn't you?" In this paradigm-shifting book, former Unilever CEO Paul Polman and sustainable-business guru Andrew Winston provide a model to help leaders build companies that contribute more to the world than they use or take-that is, net positive companies. They bypass the last gasps of denial to show how purpose and profits are inextricably linked and how collective action can deliver the scale of change and transformation the world needs. Net Positive outlines the principles and practices for surviving and thriving, based on the experience of one world-leading company, Unilever, and other groundbreaking global organizations. This essential book is for leaders, executives, managers, and professionals who want to succeed, but know that winning requires caring deeply about serving the world. Building a net positive company is the key, and this book shows the way"-